COMPENSATION OF THE DIGITAL SERVOSYSTEM CIRCULAR TRACKING TRANSITION ERROR - A. G. Stryzhniou; G. V. Lednik; A. A. Shykhau; A. N. Rusakovich (Informatika)
The paper presents a new algorithm for digital servosystem circular tracking transition error compensation. This algorithm is easily realized and ensures high system stability in the circular mode of operation with oscillating perturbations. Comparative assessment of this algorithm with other solving procedures for this problem is made. Digital modeling is applied to verify the effec-tiveness of this algorithm. A block diagram that realizes this algorithm is presented to be used in a practical application.